A Polymorphism in the BDNF Gene (rs11030101) is Associated With Negative Symptoms in Chinese Han Patients With Schizophrenia - Ping, Junjiao; Zhang, Jie; Wan, Jing; Huang, Caiying; Luo, Jiali; Du, Baoguo; Jiang, Tingyun (Frontiers in Genetics, 2022)
Objective: This study aimed to investigate the association between brain-derived neurotrophic factor (BDNF) and cyclic adenosine monophosphate response element binding protein (CREB) gene polymorphisms and schizophrenia. Methods: This study used a case-control design, and diagnoses were made based on the Diagnostic and Statistical Manual of Mental Disorders-Fifth Edition criteria. One hundred and thirty-four patients with schizophrenia were recruited from the Third People’s Hospital of Zhongshan City from January 2018 to April 2020. Sixty-four healthy controls were recruited from the same region. Genotypes at the BDNF gene single nucleotide polymorphisms rs11030101, rs2030324, and rs6265 and the CREB gene single nucleotide polymorphisms rs6740584 and rs2551640 were determined using a MassARRAY mass spectrometer. Linkage disequilibrium and haplotype analyses were performed, and genotype and allele frequencies were compared between groups. The positive and negative symptom scale (PANSS) was used to evaluate the association between the BDNF and CREB gene polymorphisms and schizophrenic symptoms. Results: There was no significant difference in genotype or allele frequencies for rs11030101, rs2030324, rs6265, rs6740584, or rs2551640 between schizophrenic patients and controls (P > 0.05). In addition, there were no significant differences in rs11030101, rs2030324, rs6265, rs6740584, or rs2551640 genotype frequencies between the two groups in the dominant, recessive, or over-dominant models (P > 0.05). Three loci in the BDNF gene and two loci in the CREB gene were in a state of strong linkage disequilibrium. The frequency of haplotype AAC (rs11030101/rs2030324/rs626), composed of three loci in the BDNF gene, was significantly increased in schizophrenic patients compared with control subjects. There were significant differences in the subscores of PANSS for negative symptoms, in patients with different rs11030101 genotypes of the BDNF gene (P < 0.05). There was also significant differences in the PANSS scores for the general symptom G12 (judgment and lack of insight) in patients with different rs6265 genotypes of the BDNF gene (P < 0.05). Conclusion: The BDNF gene rs11030101/rs2030324/rs626 AAC haplotype was potentially associated with an increased risk of schizophrenia. In addition, genotypes at the rs11030101 and rs6265 loci may affect the negative symptoms and general symptoms of schizophrenic patients, respectively.